2021
DOI: 10.1002/biot.202100231
|View full text |Cite
|
Sign up to set email alerts
|

Rational engineering and applications of functional bioadhesives in biomedical engineering

Abstract: For the past decades, several bioadhesives have been developed to replace conventional wound closure medical tools such as sutures, staples, and clips. The bioadhesives are easy to use and can minimize tissue damage. They are designed to provide strong adhesion with stable mechanical support on tissue surfaces. However, this monofunctionality of the bioadhesives hinders their practical applications. In particular, a bioadhesive can lose its intended function under harsh tissue environments or delay tissue rege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 164 publications
0
6
0
Order By: Relevance
“…NHS ester modification to the hydrogel enables it to form covalent bonding with tissue surfaces containing primary amine groups. [ 3 ] Critically, the toughness of the hydrogel allows it to endure strong covalent adhesion, thereby preventing cohesive failure. Figure S11 (Supporting Information) shows a photograph of the NHS‐functionalized hydrogel adhered to porcine skin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…NHS ester modification to the hydrogel enables it to form covalent bonding with tissue surfaces containing primary amine groups. [ 3 ] Critically, the toughness of the hydrogel allows it to endure strong covalent adhesion, thereby preventing cohesive failure. Figure S11 (Supporting Information) shows a photograph of the NHS‐functionalized hydrogel adhered to porcine skin.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, bioadhesive glues, including fibrin glue and cyanoacrylate, are primarily used clinically. [ 3 ] Their liquid‐like properties allow them to seamlessly penetrate the irregular rough geometries of tissue surfaces. Then, the penetrated glues are cured to ensure cohesion.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, conformally attaching devices made of dry and rigid materials to soft and moist tissue surfaces is highly challenging. In this regard, various studies have reported adhesive materials to implement stable device-tissue interfaces . In this section, we provide the most recent and widely reported adhesive materials for bioelectronics classified as (1) mussel-inspired, (2) bioinspired architectures, and (3) slug-inspired.…”
Section: Interfacial Compatibilitymentioning
confidence: 99%
“…A very sticky but viscous material will plastically deform before it debonds from a substrate, while a tougher material will manage to overcome adhesive forces during peeling. 18,19 1…”
Section: Adhesion and Interface Mechanicsmentioning
confidence: 99%